Implementasi Program Transisi Dari Paud Ke SD Di TK Bina Vita Palembang - Anisah Febrianti; Nyayu soraya; Muhtarom (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2025)
This study aims to describe the implementation of the transition program from Early Childhood Education (PAUD) to Elementary School (SD) at TK Bina Vita Palembang. This transition is a crucial process that influences children's readiness to enter primary education. The study uses a qualitative approach with descriptive methods. Data collection techniques include observation, interviews, and documentation involving the principal, teachers, and parents of students. The results show that the implementation of the transition program involves various activities designed to stimulate children's academic, social-emotional, and independence readiness. Transition activities include introducing the elementary school environment, establishing daily routines, and involving parents in supporting the adaptation process. Challenges encountered include limited facilities and a lack of parental understanding regarding the importance of the transition program. Efforts to address these challenges include improving communication between the school and parents as well as providing training for teachers. The study concludes that a well-structured and continuous transition program can optimally support children's readiness to enter elementary education